ANAESTHESIOLOGY AND INTENSIVE CAREThe influence of epidural anesthesia on the electrical activity of heart atria - Twardowski, Pawel; Owczuk, Radoslaw; Wujtewicz, Magdalena A.; Wojciechowski, Jacek; Marjanski, Tomasz; Marciniak, Andrzej; Wujtewicz, Maria (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : High thoracic epidural anesthesia (TEA) causes blockade of sympathetic fibers involved in innervation of the heart (segments T1-T4), which results in changes of cardiac electrophysiology. The anti-arrhythmic effects of TEA on supraventricular arrhythmias, mainly atrial fibrillation, are controversial. The aim of the study was to assess the influence of epidural anesthesia on the electrical function of heart atria, including proven markers of increased risk of perioperative atrial fibrillation, such as P wave dispersion and P wave maximum duration. Material and methods: The study involved 50 male patients, without a history of previous heart diseases, scheduled for elective surgical procedures. Patients received thoracic epidural anesthesia (group T, n = 25) or lumbar epidural anesthesia (group L, n = 25). The measurements were obtained from a continuous recording of ECG before epidural anesthesia and after the detection of blockade (T1 or T8 segment sensory block in groups T and L, respectively). Results : The statistical analysis of electrocardiographic parameters, including the maximum, minimum and mean P wave duration; P wave dispersion; the maximum, minimum and mean PR interval duration; and PR interval dispersion, did not show any inter- or intragroup differences at selected time points. Conclusions : Regardless of its location, epidural anesthesia and sympathetic blockade associated with this procedure do not significantly affect the electrical functions of the cardiac atria reflected in superficial ECG, including the electrocardiographic parameters that are considered to be markers of increased risk of perioperative atrial fibrillation, such as P wave dispersion and its maximum duration.